Is it beneficial to have chirp stimuli in vestibular evoked myogenic potential (VEMP) testing? - MR Abdallatif, Athar; Wan Mohamad, Wan Najibah; Salim, Rosdan; Mohd Sakeri, Nurul Syarida; Dzulkarnain, Ahmad Aidil Arafat; Zakaria, Mohd Normani (Nova Science Publisher, 2022)
Vestibular evoked myogenic potential (VEMP) is commonly used to measure the function of otolith organs in clinical settings. Stimuli such as low frequency tone bursts are typically utilized to record VEMP. More recently, there has been an interest to study the usefulness of chirp stimuli in the VEMP testing. Developed primarily for auditory brainstem response (ABR) recording, chirp stimuli have been used to study VEMP in normal and vestibular disordered subjects. In this paper, relevant study findings on VEMP are reviewed as intended. Depending on the types of chirps, the amplitudes of chirp-evoked VEMP appear higher than those of other stimuli. The commercially available narrow band CE-chirps produce the shortest VEMP latencies. Nevertheless, contradictory outcomes have been reported by other studies, in which further research is warranted. Moreover, information on the diagnostic usefulness of chirp-evoked VEMP when assessing those with vestibular disorders is limited, and this is subject to further studies.